The IDENTIFIKASI POTENSI WISATA BUDAYA & SEJARAH SEBAGAI KONSEP PEMBANGUNAN DESA WISATA BOOI MALUKU TENGAH - Tauran, Elviaty Helinda (Jurnal Pariwisata Indonesia, 2025)
The shift from mass tourism to alternative tourism is oriented towards activities centred on natural or local cultural experiences, with the primary aim of enhancing awareness, adventure, and learning. In light of this trend, the government of Booi village on Saparua Island in Central Maluku has begun to pay attention to the development of tourism in Booi by initiating the formulation of a tourism development plan for the area. This research employs a qualitative descriptive research method, wherein the data presented predominantly takes the form of descriptions regarding the types and characteristics of potential tourist attractions (natural, cultural, artificial) obtained through observations, interviews, focus group discussions, literature reviews, and document examinations. Booi village possesses distinctive potential and uniqueness in its tourist attractions, notably the opportunity to experience the unique lifestyle and traditions of the Booi community, encompassing activities such as local living patterns, agricultural practices, and fishing. Based on the previously discussed identification of tourism potential, it is evident that Booi village meets several criteria for tourism development. The findings of the research indicate that significant opportunities for tourism development in Booi are predominantly characterised by Cultural Tourist Attractions, specifically Historical and Cultural Tourism. In the development of a tourist village in Booi, it is anticipated that the concept of Community-Based Tourism will be employed, whereby management and operations are conducted by the local community, alongside the principles of sustainable tourism.